ANALISIS PERTANGGUNGJAWABAN PIDANA BAGI ANGGOTA POLRI YANG MELAKUKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Sinta Ayu Lestari; Hery Firmansyah (Fakultas Hukum Universitas Tarumanagara, 2019)
In Indonesia the problem of drug abuse and illicit trade continues to increase, worrying and endangering people's lives. Based on “Law Number 35 of 2009 concerning Narcotics which supersedes Law Number 22 Year 1997”, it has been regulated regarding the prohibition on the use of narcotics which are carried out without permission. In the case of narcotics abuse there are law enforcement officers who handle one of them, the police. The police as the executor and law enforcer have the duty to safeguard security and prevent and eradicate criminal acts as stipulated in the “Republic of Indonesia Police Chief Regulation Number 14 of 2011 concerning the Professional Code of Ethics of the Republic of Indonesia National Police”. In fact, there is a case in Decree “Number 1057 / Pid.Sus / 2018 / PN.Jkt.Tim and Decree Number 906 / Pid.Sus / 2018 / PN.Jkt.Tim”. where members of the police commit criminal acts of narcotics abuse. What is the mechanism of the legal process? and What is the criminal responsibility for members of the police who commit criminal acts of narcotics abuse? The author uses the normative juridical legal method and uses interview data as supporting data. The results reveal that the legal process for police officers who commit narcotics crimes similar to justice for ordinary people is in accordance with the Criminal Procedure Code, the difference is that if there is a process within the police, the police must take into consideration the profession as law enforcement in incriminating matters.